Advancements in formulations and technologies for colon-targeted drug delivery - Rana, Ritik Singh; Ale, Yogita; Pant, Pankaj; Kukreti, Neha; Jakhmola, Vikash (Journal of Applied Pharmaceutical Research, 2025)
Background: Colonic administration of drugs may enhance drug absorption, reduce adverse reactions, and facilitate delivery to specific therapeutic targets. Objective: Delivering pharmaceuticals to the colon poses challenges that require innovative formulation strategies. Methodology: Various formulation approaches have been explored for colon-targeted drug delivery systems. These approaches target the colon using formulation components that interact with GI physiology parameters such as pH, colonic flora, and enzymes. Result and Discussion: The article discussed the various research studies conducted for colon targeting involving novel strategies such as pH-dependent, enzyme-dependent, Ligand-Receptor-based, new technologies, Phloral, and magnetically derived approaches. It also explored the translational technologies, such as in vivo, in vitro, and in silico, which expedite the transition from fundamental research to clinical application and enhance therapeutic outcomes. Conclusion: In conclusion, the most relevant preclinical studies, encompassing in vitro, in vivo, and in silico research, are delineated to facilitate the strategic advancement of novel colon-targeted therapeutics.